Odpowiedzi

2009-11-01T18:11:47+01:00
Y=x²-4x+3
y=2x-6

Stąd:
x²-4x+3 = 2x - 6
x² - 6x + 9 = 0
(x - 3)² = 0
x - 3 = 0
x = 3

y = 2x - 6
y = 2 * 3 - 6 = 0

Ostatecznie
x = 3
y = 0
2009-11-01T18:31:35+01:00
Y =x^2 -4x +3
y =2x - 6
------------------
x^2 -4x +3 =2x-6 i y = 2x - 6
x^2 -6x + 9 = 0 i y = 2x - 6
( x - 3)^2 = 0 i y = 2x - 6
Odp.
x =3 i y =0
2009-11-01T19:41:14+01:00
Y=X do kwadratu-4x+3
y=2x-6

x do kwadratu -4x+3=2x-6
x do kwadratu-6x+9=0
(x-3)do kwadratu=0
x-3=0
x=3
y=2x-6
y=2x3-6=0

x=3
y=0